Antecedents of E-Loyalty and its Impact to Online Repurchase Intention - Putri Utami Vallen; Ferdi Antonio (Jurnal Manajemen Bisnis, 2022)
Research aims to examined further affect from application design, customer services, fulfillment, responsiveness, compensation, contact, e-service quality, e-WOM, e-recovery on e-loyalty and its impact to online repurchase intention. Data analysis method used PLS-SEM through total of 164 respondents Sayurbox application's users. The finding showed from nine antecedents, likewise from e-loyalty mediating variable, eight variables had significant affect to online repurchase intention and not included contact variable which appears not significant. The strongest affect came from responsiveness and application design. Meanwhile, the direct affect on e-loyalty revealed to be the strongest by e-recovery.